Separando os efeitos diretos e indiretos da complexidade e heterogeneidade de habitat sobre a riqueza de espécies e abundância de macroinvertebrados aquáticos. - Cunha, Eduardo Ribeiro da (2013)
Both habitat complexity and habitat heterogeneity are known to positively affect abundance and species richness. Mechanisms suggested to underlying these patterns are different between both factors: complexity increase food and refuge availability, and heterogeneity provide niche complementarily. We varied complexity and heterogeneity in small patches of artificial macrophytes (25cm2) to assess the contribution of these variables on abundance and species richness of associated macroinvertebrates. We additionally measured chlorophyll-a from colonizing periphytic algae as a complementary variable to explain macro-invertebrate abundance; chlorophyll-a and individual abundance was complementarily used to explain species richness. We used linear regressions and Akaike Information Criterion to assess these relationships. Our results show that species richness of macroinvertebrates is positively associated with habitat complexity, although individual abundance is the best variable explaining species richness. Individual abundance is greatly influenced by energy availability, represented by chlorophyll-a, which increases with habitat complexity. Heterogeneity does not have any substantial effects on species richness or individual abundance. These results suggests that, habitat complexity, by underlying mechanisms (e.g., food and refuge availability), is more important than habitat heterogeneity to explain increasing species richness and individual abundance in small spatial scales.